2015
DOI: 10.1155/2015/164206
|View full text |Cite
|
Sign up to set email alerts
|

An In Vivo Study of Low-Dose Intra-Articular Tranexamic Acid Application with Prolonged Clamping Drain Method in Total Knee Replacement: Clinical Efficacy and Safety

Abstract: Background. Recently, combined intra-articular tranexamic acid (IA-TXA) injection with clamping drain method showed efficacy for blood loss and transfusion reduction in total knee replacement (TKR). However, until now, none of previous studies revealed the effect of this technique on pharmacokinetics, coagulation, and fibrinolysis. Materials and Methods. An experimental study was conducted, during 2011-2012, in 30 patients undergoing unilateral TKR. Patients received IA-TXA application and then were allocated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Some authors proposed that due to the lack of “self-tamponade” effect, the use of drains might be associated with an elevated amount of total blood loss; meanwhile, blood perfusion around the wound reactively increases within hours after operation and therefore the drain tubes were advised to be clamped for about 4 to 6 hours. [ 31 , 32 ] Although we did not observe a significant difference in calculating blood loss or hemoglobin drop between the drainage group and the nondrainage group, elevated rate of postoperative homologous blood transfusion did correlate with the insertion of closed suction drains. The plausible reason is the heterogeneous and sometimes subjective criteria for transfusion.…”
Section: Discussionmentioning
confidence: 61%
“…Some authors proposed that due to the lack of “self-tamponade” effect, the use of drains might be associated with an elevated amount of total blood loss; meanwhile, blood perfusion around the wound reactively increases within hours after operation and therefore the drain tubes were advised to be clamped for about 4 to 6 hours. [ 31 , 32 ] Although we did not observe a significant difference in calculating blood loss or hemoglobin drop between the drainage group and the nondrainage group, elevated rate of postoperative homologous blood transfusion did correlate with the insertion of closed suction drains. The plausible reason is the heterogeneous and sometimes subjective criteria for transfusion.…”
Section: Discussionmentioning
confidence: 61%
“…There is, however, evidence that the combined use of TXA and clamped drains is more effective in reducing blood loss compared to TXA or drain to clamping alone [41] . The choice of clamping the drainage for 3 hours was based on the evidence that this timing optimizes the action of IA TXA [42] and follows the evidence that the half-life of IA TXA has been shown to be 3 hours [43] , avoiding, at the same time, the risk of clots formation that could obstruct the drain, in case of prolonged clamping (it is the authors' experience that this happen when drainage is kept clamped for more than 3 hours). In addition, we insufflated the tourniquet for a short time, because there is evidence that the combined use of tourniquet application and TXA administration provides advantages in terms of operative time and bleeding control [44] , [45] .…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta‐analyses have shown that various topical dosing regimens were effective. They reported a wide range of 0.25–3 g in a single dose and of 5 min to 12 h for the drug contact time . However, the optimal regimen remains undetermined.…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta-analyses have shown that various topical dosing regimens were effective. They reported a wide range of 0.25-3 g in a single dose and of 5 min to 12 h for the drug contact time [12][13][14]. However, the optimal regimen The conventional meta-analysis is limited by pooling of data at different time points and large intertrial variability (shown in Figure 2A) in the drainage volume of the placebo group across studies.…”
Section: Discussionmentioning
confidence: 99%